2017
DOI: 10.3390/rs9050418
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Latest MODIS GPP Products across Multiple Biomes Using Global Eddy Covariance Flux Data

Abstract: Abstract:The latest MODIS GPP (gross primary productivity) product, MOD17A2H, has great advantages over the previous version, MOD17A2, because the resolution increased from 1000 m to 500 m. In this study, MOD17A2H GPP was assessed using the latest eddy covariance (EC) flux data (FLUXNET2015 Dataset) at eighteen sites in six ecosystems across the globe. The sensitivity of MOD17A2H GPP to the meteorology dataset and the fractional photosynthetically-active radiation (FPAR) product was explored by introducing sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 50 publications
8
73
0
Order By: Relevance
“…When compared to the site level of flux tower-based GPP (Figure 6), the slope values in most sites of the study regions were also less than 1.0, except for some desert ecosystem sites. This showed that the MOD17 product underestimated GPP in most high productivity sites of cropland, grassland, and forest ecosystems in the arid region, but overestimated GPP at some low productivity sites of desert ecosystems compared with tower-based GPP, consistent with the results of Reference [12] and Reference [27].…”
Section: Evaluations Of the Mod17a2h Products Over Diversity Ecosystesupporting
confidence: 83%
See 3 more Smart Citations
“…When compared to the site level of flux tower-based GPP (Figure 6), the slope values in most sites of the study regions were also less than 1.0, except for some desert ecosystem sites. This showed that the MOD17 product underestimated GPP in most high productivity sites of cropland, grassland, and forest ecosystems in the arid region, but overestimated GPP at some low productivity sites of desert ecosystems compared with tower-based GPP, consistent with the results of Reference [12] and Reference [27].…”
Section: Evaluations Of the Mod17a2h Products Over Diversity Ecosystesupporting
confidence: 83%
“…To date, MODIS has issued multiple versions of GPP [14,16]. Currently, the MOD17 product has been updated to Collection 6 (C6), which has improved the algorithm parameters and forcing data of previous collections [15,17], as the spatial resolution has increased from 1000 m to 500 m. A large number of studies have validated the capacity of MODIS GPP products with eddy covariance (EC) measurements across multiple biomes, such as forests [18,19], shrublands [20], grasslands [21,22], savanna [23], croplands [24], and across biomes [12,[25][26][27]. However, most of these studies validated previous versions of MODIS GPP products (i.e., Collection 4 and 5).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationships between the LSWI-GPP and LSWI-NPP were stronger because the strong correlation between the EVI and LSWI supported this relationship. In addition, previous studies confirmed that the potential of this method for estimating terrestrial GPP is similar to that when using the MOD17 GPP and NPP datasets [54,55]. No measured data were available in the fire study area, so this study could not easily conclude that the EVI had the potential to estimate terrestrial GPP during vegetation recovery.…”
Section: Relationship Of Modis Products To the Gpp And Nppmentioning
confidence: 63%